Removal of refractory organic substances with activated carbon and advanced oxidation techniques for water purification : technology review and regeneration experiment - Xu, Yanchen. (2011)
Nitrogen-doped titanium dioxide supported on AC (N-TiO2/AC) composite potentially serves as solar-regenerable composites. This promising material was synthesized to explore its potential application in water treatment. To characterize this material, the X-ray diffractometer (XRD), QuantaChrome Autosorb-1 Analyzer, X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM) and transmission electron microscope (TEM) were used. The investigation of the regeneration efficiency (RE) as achieved by this composite was set as the aim of this project. To accomplish the entire regeneration process, the author was involved in synthesizing, characterizing the composite, evaluating the adsorption capacity and investigating the different governing parameters that may influence RE. The trend of the regeneration efficiency under different parameters such as N-TiO2/AC composite dosages, operating temperature, light intensity and cycles of reuse was obtained. N-TiO2/AC is able to achieve reasonable regeneration efficiency with low capital costs, low facility requirement and low environmental hazard which cannot be all achieved by other regeneration methods. This composite presents its good ability and foreground in real application for water reclamation.